Assessment of the functional results of hemiarthroplasty in geriatric individuals with unstable intertrochanteric femur fractures - Tuse, Sushant S.; Bhutani, Prashant; Matin, Aamir (International Journal of Research in Orthopaedics, 2023)
Background: The objective of our study is to measure early weight bearing, mobilization, rapid rehabilitation, complications in unstable intertrochanteric femur after hemiarthroplasty fractures in elderly patients. Methods: Prospective and retrospective, non-randomized study was conducted to assess functional results of hemiarthroplasty in elderly individuals with unstable intertrochanteric femur fractures following surgery in patients who underwent surgery from 2019 to 2021 in department of orthopaedics of Seth Nandlal Dhoot Hospital, Aurangabad. Out of total 44 participants, there were 16 males and 28 females with mean age of 79.54 years of study participants. The patients were evaluated radiologically with routine X-rays i.e. pelvis with both hip joint anteroposterior (AP) view and affected side hip lateral view and clinically early weight bearing, mobilization, rapid rehabilitation and complication with Harris hip score. Results: In our study we observed good result of 86.53±5.73 mean Harris hip score at the end of 1 year was following surgery in 44 study participants who underwent hemiarthroplasty in unstable intertrochanteric femur fractures in elderly patients. Conclusions: Primary hemiarthroplasty offers an essentially pain-free movable joint and is a preferable mode of treatment for older osteoporotic patients who suffers from unstable intertrochanteric femur fractures. Hemiarthroplasty allows for early mobilization and offers rapid stability and mobility, preventing the issues associated with recumbency. Hemiarthroplasty has a lower rate of complications and revision surgery than fixation. According to the Harris hip score, primary bipolar hemiarthroplasty results in a good functional outcome, but long-term monitoring is necessary.